A Comparative Study of Malaysian and Indonesian Students’ Entrepreneurial Characteristics and Career Choices Resulting from the Digital Economy - Nadiah Abd Hamid; Florentina Kurniasari; Hakimah ‘Aisyah Mohamad Taib; Tengku Fairuz Tengku Embong; Nor Hasnah Mad Saheh; Norazah Md Azali; Nurshamimi Sabli (International Journal of Supply Chain Management, 2018)
This paper aims to identify the effects of digital economy on students entrepreneurial traits and entrepreneurship as career choices, comparatively between Malaysia and Indonesia. A sample of students was randomly selected from public universities and private universities in each country. Confirmatory Factor Analysis (CFA), which is the foundation of structural equation modeling (SEM), has been used. The results evidenced that the digital economy in both countries significantly influencing the entrepreneurial characteristics of the students. However, in Indonesia, the results are significant for all four dimensions of digital economy, while in Malaysia, only two dimensions are found to be significant namely social and cultural environment and the consumer and business adoption. Not only that, despite the entrepreneurial traits the students in Malaysia possessed, in contrast with Indonesian university students, it is discovered that they are reluctant to become entrepreneurs in future. Hence, both Malaysian and Indonesian governments need to keep on supporting the development of digital economy to foster the entrepreneurial traits among students. Plus, the lessons on entrepreneurship can be introduced as important subjects in universities in both countries, especially in Malaysia, to boost students entrepreneurial interest.